2005
DOI: 10.1152/jn.00218.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Restriction Suppresses Neurogenesis Induced by Hippocampus-Dependent Learning

Abstract: Sleep deprivation impairs hippocampal-dependent learning, which, in turn, is associated with increased survival of newborn cells in the hippocampus. We tested whether the deleterious effects of sleep restriction on hippocampus-dependent memory were associated with reduced cell survival in the hippocampus. We show that sleep restriction impaired hippocampus-dependent learning and abolished learning-induced neurogenesis. Animals were trained in a water maze on either a spatial learning (hippocampus-dependent) ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
143
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(156 citation statements)
references
References 56 publications
10
143
1
1
Order By: Relevance
“…This may be a result of procedural differences, including the age of the animals, the housing conditions, or antibody used for BrdU detection. However, the findings are generally consistent with our previous study and others as well (Dobrossy et al 2003;Drapeau et al 2003;Hairston et al 2005;Kee et al 2007). One study did report a reduction in cell number after spatial training (Mohapel et al 2006), but they used multiple injections of BrdU, making it difficult to assess how many cells are generated versus how many survive after training.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This may be a result of procedural differences, including the age of the animals, the housing conditions, or antibody used for BrdU detection. However, the findings are generally consistent with our previous study and others as well (Dobrossy et al 2003;Drapeau et al 2003;Hairston et al 2005;Kee et al 2007). One study did report a reduction in cell number after spatial training (Mohapel et al 2006), but they used multiple injections of BrdU, making it difficult to assess how many cells are generated versus how many survive after training.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the increase in cell survival was not induced by motor activity or the stress of the training procedure. Since the initial report, this phenomenon and related ones have been reported (Kempermann and Gage 2002;Dobrossy et al 2003;Drapeau et al 2003;Hairston et al 2005;Kee et al 2007). …”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Common targets of both stress and sleep deprivation include various growth factors (35)(36)(37)(38). Adult neurogenesis is known to be regulated by such extracellular signals (39), although the potential protracted effects of stress or sleep deprivation on neurotrophic levels have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…However, the direction of the effect is not always the same. For example, it has been shown that training with trace eyeblink conditioning, spatial learning in the Morris water maze and conditioned food preference increase the number of newborn cells in the DG of adult rats (Gould et al, 1999c;Ambrogini et al, 2000;Lemaire et al, 2000;Dobrossy et al, 2003;Leuner et al, 2004c;Hairston et al, 2005;Olariu et al, 2005). These effects appear to be specific to learning that requires the hippocampus.…”
Section: Evidence In Favormentioning
confidence: 99%